Analisis Problematika Pembelajaran Daring dan Pengaruhnya Terhadap Motivasi Belajar Siswa Kelas IV SDN Bugangan 01 Semarang - Dewi Suciati; Ikha Listyarini; Qoriati Mushafanah (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
Online learning is learning that in its application utilizes various digital technology sources through internet network access without involving direct interaction so that it is able to cover a wider group. The purpose of this study was to analyze the problems of online learning and the effect of online learning problems on students' learning motivation. The research method used in this research is a descriptive qualitative method. The results of the study show that the problem of online learning is incomplete student attendance. unsupported networks, lack of online learning facilities and infrastructure, teachers find it difficult to get feedback from students. The effect of online learning problems on learning motivation, learning motivation has decreased when online learning is 22% of students who like online learning and 78% of students prefer face-to-face learning.